Age-related deregulation of TDP-43 after stroke enhances NF-κB-mediated inflammation and neuronal damage - Sai Sampath Thammisetty; Jordi Pedragosa; Yuan Cheng Weng; Frédéric Calon; Anna Planas; Jasna Kriz (Journal of Neuroinflammation, 2018)
Abstract Background TDP-43 has been identified as a disease-associated protein in several chronic neurodegenerative disorders and increasing evidence suggests its potentially pathogenic role following brain injuries. Normally expressed in nucleus, under pathological conditions TDP-43 forms cytoplasmic ubiquitinated inclusions in which it is abnormally phosphorylated and cleaved to generate a 35 and a 25 kDa C-terminal fragments. In the present study, we investigated age-related expression patterns of TDP-43 in neurons and glia and its role as modulator of inflammation following ischemic injury. Methods Wild-type and TDP-43 transgenic mice of different age groups were subjected to transient middle cerebral artery occlusion. The role of TDP-43 in modulation of inflammation was assessed using immunofluorescence, Western blot analysis, and in vivo bioluminescence imaging. Finally, post-mortem stroke human brain sections were analyzed for TDP-43 protein by immunohistochemistry. Results We report here an age-related increase and formation of ubiquitinated TDP-43 cytoplasmic inclusions after stroke. The observed deregulation in TDP-43 expression patterns was associated with an increase in microglial activation and innate immune signaling as revealed by in vivo bioluminescence imaging and immunofluorescence analysis. The presence of ubiquitinated TDP-43 aggregates and its cleaved TDP-35 and TDP-25 fragments was markedly increased in older, 12-month-old mice leading to larger infarctions and a significant increase in in neuronal death. Importantly, unlike the hallmark neuropathological features associated with chronic neurodegenerative disorders, the TDP-43-positive cytoplasmic inclusions detected after stroke were not phosphorylated. Next, we showed that an increase and/or overexpression of the cytoplasmic TDP-43 drives the pathogenic NF-κB response and further increases levels of pro-inflammatory markers and ischemic injury after stroke in age-dependent manner. Finally, analyses of the post-mortem stroke brain tissues revealed the presence of the cytoplasmic TDP-43 immunoreactive structures after human stroke. Conclusion Together, our findings suggest that the level of cytoplasmic TDP-43 increases with aging and may act as an age-related mediator of inflammation and neuronal injury after stroke. Thus, targeting cytoplasmic TDP-43 may have a therapeutic potential after stroke.